Exploiting Plant–Natural Enemy Interactions: Selection and Evaluation of Plants for the Improvement of Biological Control - Hipolito Cortez-Madrigal (Insects)
To identify and select wild plant species as a source of nectar and pollen for the conservation of natural enemies (NEs), with an emphasis on parasitic Hymenoptera, entomological samplings were carried out on the inflorescences of plants in the northwest of Michoacán, Mexico, in 2020. The species were selected based on the number and diversity of NEs, flowering period, phytosanitary risks (pests), and ease of multiplication. Of more than 27 plant species, NEs were recorded in 24. The Eulophid family represented 74.14% of 23 families of parasitoids recorded, and in 19 of the 23 plant species with parasitoids, the eulophid family was the most prevalent. Thirteen plant species were selected; annual species such as Tithonia tubaeformis and Stevia serrata stand out. Among the shrubs, Senecio salignus and Baccharis salicifolia stand out, as do trees such as Viguiera quinqueradiata, Thouinia villosa and Buddleja parviflora. Serjania racemosa and Phytolacca icosandra stand out for their long flowering period (>5 months) and the wide diversity of beneficial entomofauna. They are plants that reproduce easily and have a low phytosanitary risk to crops. The presence of flowering plants in agroecosystems could attract and maintain NE populations, even before pests arrive, with predictable benefits for integrated pest management.